2017
DOI: 10.1038/s41598-017-18139-7
|View full text |Cite
|
Sign up to set email alerts
|

Tracing halogen and B cycling in subduction zones based on obducted, subducted and forearc serpentinites of the Dominican Republic

Abstract: Serpentinites are important reservoirs of fluid-mobile elements in subduction zones, contributing to volatiles in arc magmas and their transport into the Earth’s mantle. This paper reports halogen (F, Cl, Br, I) and B abundances of serpentinites from the Dominican Republic, including obducted and subducted abyssal serpentinites and forearc mantle serpentinites. Abyssal serpentinite compositions indicate the incorporation of these elements from seawater and sediments during serpentinization on the seafloor and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 58 publications
2
24
0
Order By: Relevance
“…Serpentinites formed close to spreading centres have I/Cl similar to average crust and 40 Ar/ 36 Ar of close to the atmospheric/seawater value of 296 (Table 2 and In contrast with Cl, Br and I, which have high solubilities in seawater and sedimentary pore waters, the majority of serpentinites investigated have low concentrations of <20 ppm F ( Fig 3; Table 1) and similarly low F concentrations have been reported for oceanic serpentinites preserved in the Dominican Republic ophiolite (Pagé and Hattori, 2017). The low F content of many oceanic serpentinites is explained because seawater contains only 1.3 ppm F (Drever, 1997), and even though carbonate rich sediments can contain 1000-1500 ppm F (Rude and Aller, 1991), the low solubility of F under diagenetic conditions (Seyfried and Ding, 1995) means it retains a low seawater-like concentration in most sedimentary pore waters (Gieskes et al, 2002).…”
Section: The Origin Of Serpentinising Fluidssupporting
confidence: 61%
See 4 more Smart Citations
“…Serpentinites formed close to spreading centres have I/Cl similar to average crust and 40 Ar/ 36 Ar of close to the atmospheric/seawater value of 296 (Table 2 and In contrast with Cl, Br and I, which have high solubilities in seawater and sedimentary pore waters, the majority of serpentinites investigated have low concentrations of <20 ppm F ( Fig 3; Table 1) and similarly low F concentrations have been reported for oceanic serpentinites preserved in the Dominican Republic ophiolite (Pagé and Hattori, 2017). The low F content of many oceanic serpentinites is explained because seawater contains only 1.3 ppm F (Drever, 1997), and even though carbonate rich sediments can contain 1000-1500 ppm F (Rude and Aller, 1991), the low solubility of F under diagenetic conditions (Seyfried and Ding, 1995) means it retains a low seawater-like concentration in most sedimentary pore waters (Gieskes et al, 2002).…”
Section: The Origin Of Serpentinising Fluidssupporting
confidence: 61%
“…Recent studies have suggested that up to ~90% of non-radiogenic Ar, Kr and Xe and most of the heavy halogens (Cl, Br, I) have subducted origins in the Earth's mantle (Holland and Ballentine, 2006;Holland et al, 2009;Mukhopadhyay, 2012;Caracausi et al, 2016;Kendrick et al, 2017). However, relatively few studies have investigated the combined behaviour of multiple halogens and/or noble gases during prograde metamorphism (John et al, 2011;Kendrick et al, 2015;Pagé et al, 2016;Pagé and Hattori, 2017),…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations